Imaging and chemical methods for preventing the risk of coal self-ignition - Tomescu, Cristian; Cioclea, Doru; Gherghe, Ion; Boanta, Cornel; Rădoi, Florin (Журфонд, 2020)
Important information for drawing up the risk scenario and the plan for preventing spontaneous ombustion in coal mines are provided by knowledge on the coal’s self-ignition tendency gained from laboratory determinations carried out for establishing self-ignition parameters and for the classification of coal from this point of view. This paper provides an analysis on the concerned preventive triangle: a classification on the selfignition risk, applications of preventive methods in coal mining thermography and the instrumentation of inhibiting water solutions as measures for preventing coal self-ignition.

Апріорне знання ризику самозаймання шляхом лабораторних визначень параметрів самозаймання та класифікації вугілля з цієї точки зору, забезпечує необхідну інформацію для підготовки сценарію ризику та плану запобігання самозаймання у вугільних шахтах. Ця робота спрямована на аналіз цього профілактичного тринома: класифікація ризику самозаймання, застосування методів запобігання при видобутку вугілля, термографії та контрольно-вимірювальних приладів водних розчинів з інгібіторами, як заходів щодо запобігання самозаймання вугілля.
Візуалізація та хімічні методи для запобігання ризику самозаймання вугілля
Keywords: coal; вугілля; risk; ризик; spontaneous combustion; самозаймання; інгібітори